A Scale Model of Tension Structures in Road Tunnels to Optimize the Use of Solar Light for Energy Saving. (15th September 2011) - Peña-García, Antonio; Gil-Martín, Luisa-María; Escribano, Roberto; Espín-Estrella, Antonio
Abstract : Shifting the threshold zone of road tunnels with semitransparent tension structures has shown itself to be an effective way of saving energy in regards to electricity consumption, maintenance, and construction materials used in the electrical lighting, thus lessening negative environmental impacts. Even though the shape of the tension structure has a major influence on energy savings, the optimal type of structure for each tunnel is often difficult to determine, because experiments using real tunnels are extremely expensive. It is thus necessary to find methods of doing this that are both reliable as well as economical. In this research study, three candidate structures were set up at the portal of a scale model of a real tunnel. The energy savings in each case were analyzed and compared. As a result, it was possible to formulate a new equation that calculates the energy savings in the threshold zone.